The driving forces of bully in adolescents: a systematic review of literature in Asian country - Ibrahim, Nur Nazihah; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2022)
Bully is the intentional and repeated hostility act via physical, verbal, or cyber in which the victims cannot defend themselves. Hence, these acts of aggression have several of negative impacts towards the victim’ life (physically, emotionally and psychologically). The growing of bully incidents especially among adolescents in the school background was increasingly upsetting. More concerns and research were given to aid the victimized population leaving the bullies unattended. Hence, this review focuses on the factors that drive the school student to engage in bully. This systematic review studies the factors lead to bully incidents in selected major Asian countries namely Hong Kong, China, India, Vietnam and Malaysia. Information was extracted from SCOPUS database to find relevant reading materials which includes the inclusions and exclusion criteria in the processes. A total of 10 journals were selected to aid reviewer in analysing data for responding the three main objectives of this paper. The driving forces of bullying such as environmental influences, self-expressive, racial elements, psychological factors were discussed systematically. The statistic and pattern of bullying incidents were also identified from the selected journals. The implications of this review were also being discussed.